Wstyd dobry i zły - z perspektywy teologicznomoralnej - Zadykowicz, Tadeusz (Studia Theologica Varsaviensia, 2017)
The subject of shame appears in moral theology especially in conjunction with a reflection on marital and family life, for which – as it emphasizes – an important form of preparation is nurturing the feeling of shame, especially at the level of sexual life. Studies of moral theology rarely talk about shame negatively. Meanwhile shame, in addition to all its positive aspects, can also be bad; personally and socially destructive. Shame may have the wrong object and an exaggerated intensity. Therefore shame, like every emotion, requires formation and subjecting it to reason and will, and above all harnessing it in the service of love.